First record of a live adult heteropod Firoloida desmarestia in the Red Sea - Angulo-Preckler, Carlos; Steckbauer, Alexandra; Armelles, Isabel; Agustí, Susana; Rodrigue, Mattie; Pieribone, Vincent; Qurban, Mohammad; Duarte, Carlos M. (Frontiers in Marine Science, 2023)
Observations are essential to explore and discover the ocean. The rapid advancements in technology have revolutionized our capacity to document the ocean and its diverse array of species, pushing the boundaries of our understanding further than ever before. The central Red Sea was exposed as part of the Red Sea Decade Expedition, which took place from 04 February to 18 June 2022 aboard the R/V OceanXplorer, using underwater submersibles. Here, for the first time in the Red Sea, we reported three observations of living Firoloida desmarestia specimens, one female and two male specimens, a heteropod from the Pterotracheidae family. This shell-less mollusk has been observed in the epipelagic zone of the world’s oceans, with the exception of polar regions, suggesting a global distribution for these observations. The two males were observed swimming in the water column, while the female was close to the seabed. All three observations were detected during the morning, raising the question if these organisms use vertical migrations to reach deep-sea waters during the daytime. However, no ROV or submersible dives were conducted at night. Our results show a depth range expansion for observations of this species in the Red Sea. Furthermore, as far as we know, no adults of F. desmarestia have been reported until now in the Red Sea. During the expedition, all three specimens were found at similar depths (350, 400, and 464.5 m depth), with the female being the deepest, thus confirming the eurybathic distribution of this species. The emerging technology is progressively enhancing our understanding of these enigmatic creatures and expanding our knowledge of their fascinating adaptations and ecological roles. In addition to our fieldwork, a literature search was performed to uncover any pre-existing observational records of this species to understand its global distribution and ecological significance.